Integrasi Perangkat Lunak Spreads heet Dengan Computer Aided Design (CAD) Untuk Proses Perancangan Sebuah Super Heater Konveksi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
in the Convection Superheater design have two processes, calculation process and drawing process. Normally, it will be done by separate tim and it will take a long time relativelly. Therefore, the research start to make integration between Spreadsheet software ( for calculations ) and CAD software ( for drawing ). The research use Visual Basic for Application ( VBA ) for integration Microsoft Excell (for spreadsheet) and AutoCAD. The output of the sistem are Calculatioan data (workbook & worksheet in microsoft excell format), drawing (in AutoCAD format), and specification data of the Convection Superheater.